A methylation-dependent checkpoint by SETD7 promotes myocardial ischemic injury in mice and men. (3rd October 2022) - Ambrosini, S; Montecucco, F; Koljin, D; Akhmedov, A; Pedicino, D; Mohammed, S A; Kiss, A; Beltrami, A P; Luscher, T F; Crea, F; Ruschitzka, F; Hamdani, N; et al.
Abstract: Background: Despite appropriate revascularization strategies, a significant number of patients with myocardial infarction (MI) develop ischemic heart failure suggesting that breakthrough therapies are yet to be approved in this setting. Methylation of non-histone proteins is emerging as a central regulatory mechanism in health and disease. The methyltransferase SETD7 has been shown to methylate and alter the function of a variety of proteins in vitro, however, its function in the heart is poorly understood. Purpose: To determine the role of SETD7 in myocardial ischemic injury. Methods: Neonatal rat ventricular myocytes (NRVM) were exposed to normal glucose levels or glucose deprivation (GD) for 15 h, in the presence of the selective SETD7 inhibitor (R)-PFI-2 or its inactive enantiomer (S)-PFI-2. Western blot and real-time PCR were employed to investigate the effects of energy stress on SETD7 and the Hippo pathway, while apoptosis and oxidative stress were assessed by Caspase-3 activity assay and mitoSOX staining. YAP transcriptional activity was assessed by chromatin immunoprecipitation assay (ChIP) while its localization and methylation were examined by confocal microscopy and immunoblotting, respectively. SETD7 knockout (SETD7−/−) mice and wild-type (WT) littermates underwent myocardial ischemia-reperfusion (I/R) injury (1h coronary ligation /24 h of reperfusion) followed by assessment of cardiac function by echocardiography. Left ventricular (LV) myocardial samples were collected from I/R mice and patients with ischemic cardiomyopathy (ICM), and isolated cardiomyocytes were treated with (R)-PFI-2. Finally, SETD7 expression was also assessed in peripheral blood mononuclear cells (PBMCs) from patients with ST-elevation MI (STEMI). Results: SETD7 was activated upon energy deprivation in cultured NRVMs and methylated YAP, leading to its cytosolic retention and impaired transcription of antioxidant genes MnSOD and CAT. Pharmacological inhibition of SETD7 by (R)-PFI-2 restored YAP nuclear localization thus preventing mitochondrial reactive oxygen species (mtROS) and apoptosis. SETD7 deletion in mice attenuated I/R injury, mtROS and LV dysfunction by restoring YAP-dependent transcriptional programs. SETD7/YAP dysregulation was also observed in LV specimens from ICM patients. Moreover, in cardiomyocytes isolated from I/R mice and ICM patients, (R)-PFI-2 restored YAP nuclear localization, prevented mtROS accumulation while improving myofibrillar protein contractility and Ca2+ sensitivity. Finally, SETD7 was upregulated in PBMCs from STEMI patients and negatively correlated with the expression of MnSOD and CAT. Conclusions: SETD7-dependent methylation of YAP is an important mechanism underpinning myocardial oxidative stress and apoptosis during ischemia. Pharmacological modulation of SETD7 by (R)-PFI-2 may represent a potential therapeutic approach to prevent myocardial ischemic damage through modulation of the Hippo pathway. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): University of Zurich